Increasing mass loss from Greenland's Mittivakkat Gletscher - Mernild, S. H.; Knudsen, N. T.; Lipscomb, W. H.; Yde, J. C.; Malmros, J. K.; Hasholt, B.; Jakobsen, B. H. (The Cryosphere, 2011)
Warming in the Arctic during the past several decades has caused glaciers to thin and retreat, and recent mass loss from the Greenland Ice Sheet is well documented. Local glaciers peripheral to the ice sheet are also retreating, but few mass-balance observations are available to quantify that retreat and determine the extent to which these glaciers are out of equilibrium with present-day climate. Here, we document record mass loss in 2009/10 for the Mittivakkat Gletscher (henceforth MG), the only local glacier in Greenland for which there exist long-term observations of both the surface mass balance and glacier front fluctuations. We attribute this mass loss primarily to record high mean summer (Juneĝ€"August) temperatures in combination with lower-than-average winter precipitation. Also, we use the 15-yr mass-balance record to estimate present-day and equilibrium accumulation-area ratios for the MG. We show that the glacier is significantly out of balance and will likely lose at least 70% of its current area and 80% of its volume even in the absence of further climate changes. Temperature records from coastal stations in Southeast Greenland suggest that recent MG mass losses are not merely a local phenomenon, but are indicative of glacier changes in the broader region. Mass-balance observations for the MG therefore provide unique documentation of the general retreat of Southeast Greenland's local glaciers under ongoing climate warming.